HEDGES IN CLASSROOM SPEECHES BY ENGLISH STUDENTS IN GRADUATE PROGRAM - Yuliarti, Arina; Warsono, Warsono (Universitas Negeri Semarang, 2016)
Sometimes, students need to present learning materials in front of the class. In this classroom speech, they need to deliver their speech appropriately so that the information can be accepted well. Consequently, they often hedge their utterances. Therefore, this study was conducted to analyse the ways students use hedges in their classroom speeches. This study aimed at analysing the forms and functions of the hedges and the factors which might constrain the use of the hedges. The subjects were 15 students of graduate program majoring English Language Education in Semarang State University. Their classroom speeches were recorded as source of the data. Based on the findings, it could be identified that the students hedged their sentences during classroom speeches frequently. In average, students hedged around 58% of their entire sentences. Seven forms and four functions of hedges were used by students effectively and significantly. The students mainly hedged their sentences using approximator, introductory phrase, and modal-auxiliary verb forms. Plausibility and attributive shield functions were often used to soften their attitude toward the truth value of the information they presented. It could also be identified that there were five factors constraining the use of the hedges during their classroom speeches.